2D:4D and Self-Employment: A Preregistered Replication Study in a Large General Population Sample. (January 2022) - Fossen, Frank M.; Neyse, Levent; Johannesson, Magnus; Dreber, Anna
The 2D: 4D digit ratio, the ratio of the length of the second finger to the length of the fourth finger, is often considered a proxy for testosterone exposure in utero. A recent study reported, among other things, an association between the left-hand 2D:4D and self-employment in a sample of 974 adults. In this preregistered study, we replicate the 2D:4D results on a sample of more than 2100 adults from the German Socioeconomic Panel-Innovation Sample (SOEP-IS). We find no statistically significant associations between 2D:4D and self-employment.